Wear To Style Yourself / Rabiatul Adawiyah Rozhan - Rozhan, Rabiatul Adawiyah (2021)
This assignment is regarding Social Media Portfolio where students need to create a Facebook Page for the business online. As mine, I choose to do Wear To Style Yourself as my Facebook Page Name which is I prefer to do a business in clothing. Wear To Style Yourself provides a variety of fashion for the all categories of ages to them make their own style in their own attire. As simple as that, customers can choose which style their prefer to have either, Korean Style, English Style, Islamic Style as long as their happy and comfortable with their outfit or also we can called it OOTD, Outfit of the Day. Our target audiences is a group of people who is loving in do a fashion style especially women that are really loves to in fashion that can make them be confident when there are outside. But not forget, men also like to have their on style or outfit that are suitable for them. I also registered my own business under Go- ECommerce platform that provides comprehensive guides for micro entrepreneurs and Subject Matter Experts (SMEs) interested in growing the business through digital platforms. There are also several online training that entrepreneurs and traders can leverage to increase business knowledge. At the end of the study, I managed to get a lot of a new knowledge in doing a business that I can apply in the real business in the world. I also got to evaluate a business performance through the posting and comment from customers to improve the business in the future.